EKSISTENSI ROHIS SEBAGAI BASIS PENGUATAN PAI DI SMAN 2 SEMARANG - Imran Siregar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractThis paper presents the result of the study at State High School 2 Semarang which reveals the strengthening of PAI (Islamic Religious Education) learning by playing a role of Rohis (Mosque Family Council) as the spearhead in respondingto aspirations and student participation. The study took place from February to July 2016 using a qualitative approach. Data was collected through a checklist, interview, observation and documentation. The result of descriptive data analysis shows that the role of rohis in strengthening the PAI learning has been able to foster creativity of students through an aspirative and interesting program thus it is more intriguing the students’ interest to follow the religious deepening material as the reinforcement of regular material received in a classroom. In the process, GPAI remains the main institution in charge and the main driver of PAI learning supported by principals and teachers and parents.AbstrakTulisan ini menyajikan hasil penelitian di SMAN 2 Semarang yang mengungkap penguatan pembelajaran PAI dengan memeranankan Rohis sebagai ujung ombak dalam merespon aspirasi dan partisipasi siswa. Penelitian ini berlangsungpada bulan Februari hingga Juli tahun 2016 dengan menggunakan pendekatan kualitatif. Data dikumpulkan melalui daftar isian, wawancara, observasi dan dokumentasi. Hasil analisis data secara deskriptif menunjukkan bahwa pemeranan rohis dalam penguatan pembelajaran PAI telah dapat menumbuhkan kreatiftas siswa melalui program yang aspiratif dan menarik sehingga lebihmenggugah minat siswa untuk mengikuti materi pendalaman agama sebagai penguatan dari materi reguler yang diterima di ruang kelas. Dalam proses itu GPAI tetap menjadi penangungjawab dan penggerak utama pembelajaran PAI yang didukung oleh kepala sekolah dan para guru serta orang tua siswa.